Program Kultum Pagi di SD 52 Pangkalpinang Dalam Evaluasi Program Model Wheel - Asyraf Suryadin; Kurnia Akbar; Asoka Rahmania; Shadrina Idzni Khoirunnisa (4, 2026)
The Seventh Lecture (Kultum) religious lecture is a routine program at Elementary School (SD) 52 Pangkal Pinang, aimed at strengthening the moral and spiritual education of students in grades 1 through 6. These lectures are delivered by religious teachers or guest ustadz (Islamic religious teachers), covering themes such as Islamic teachings, morals, and daily life values, integrated into the daily curriculum. The primary goal is to shape students' character through faith, piety, and high morals. The implementation method includes interactive lectures lasting 20-35 minutes per session, followed by questions and answers and simple practices such as prayer recitation. Data was collected through direct observation, interviews with teachers and students, and behavioral impact evaluations. Results indicate an increase in student awareness of religious practices and tolerance, with active participation reaching 90%. At SD 52 Pangkal Pinang, these lectures are often combined with extracurricular activities, strengthening understanding of Islamic teachings. The main challenges are the varying ages of students and limited lesson time. The Kultum lecture program is effective in supporting the formation of a young generation with noble morals. Recommendations include developing more adaptable lecture materials and collaborating with parents to increase relevance. This abstract emphasizes the role of lectures as an important element of holistic education in elementary schools. Abstrak Kegiatan Kuliah Tujuh (Kultum) berupa ceramah keagamaan adalah program rutin di Sekolah Dasar (SD) 52 PangkalPinang, yang bertujuan memperkuat pendidikan moral dan spiritual siswa kelas 1 hingga 6. Ceramah ini disampaikan oleh guru agama atau ustadz tamu, dengan tema-tema seperti ajaran Islam, akhlak, dan nilai-nilai kehidupan sehari-hari, diintegrasikan ke dalam kurikulum harian. Tujuan utama adalah membentuk karakter siswa yang beriman, bertakwa, dan bermoral tinggi. Metode pelaksanaan mencakup ceramah interaktif selama 20-35 menit per sesi, diikuti tanya jawab dan praktik sederhana seperti bacaan doa. Data dikumpulkan melalui observasi langsung, wawancara dengan guru dan siswa, serta evaluasi dampak perilaku. Hasil menunjukkan peningkatan kesadaran beribadah dan toleransi antar siswa, dengan partisipasi aktif mencapai 90%. Di SD 52 Pangkal Pinang, ceramah ini sering dikombinasikan dengan kegiatan ekstrakurikuler, memperkuat pemahaman ajaran Islam. Tantangan utama adalah variasi usia siswa dan keterbatasan waktu pelajaran. Kegiatan Kultum ceramah efektif dalam mendukung pembentukan generasi muda yang berakhlak mulia. Rekomendasi meliputi pengembangan materi ceramah yang lebih adaptif dan kolaborasi dengan orang tua untuk meningkatkan relevansi. Abstrak ini menegaskan peran ceramah sebagai elemen penting pendidikan holistik di sekolah dasar.